Unsupervised deep learning of electrocardiograms enables scalable human disease profiling - Sam F. Friedman; Shaan Khurshid; Rachael A. Venn; Xin Wang; Nate Diamant; Paolo Di Achille; Lu-Chen Weng; Seung Hoan Choi; Christopher Reeder; James P. Pirruccello; Pulkit Singh; Emily S. Lau; et al. (npj Digital Medicine)
Abstract The 12-lead electrocardiogram (ECG) is inexpensive and widely available. Whether conditions across the human disease landscape can be detected using the ECG is unclear. We developed a deep learning denoising autoencoder and systematically evaluated associations between ECG encodings and ~1,600 Phecode-based diseases in three datasets separate from model development, and meta-analyzed the results. The latent space ECG model identified associations with 645 prevalent and 606 incident Phecodes. Associations were most enriched in the circulatory (n = 140, 82% of category-specific Phecodes), respiratory (n = 53, 62%) and endocrine/metabolic (n = 73, 45%) categories, with additional associations across the phenome. The strongest ECG association was with hypertension (p < 2.2×10-308). The ECG latent space model demonstrated more associations than models using standard ECG intervals, and offered favorable discrimination of prevalent disease compared to models comprising age, sex, and race. We further demonstrate how latent space models can be used to generate disease-specific ECG waveforms and facilitate individual disease profiling.